Effect of Cibacron blue F3GA on oligonucleotide binding site of estradiol--receptor complexes of mouse uterine cytosol. - Kumar, S A (1979)
The binding of estradiol--receptor complexes of mouse uterine cytosol to oligodeoxynucleotide celluloses is inhibited by the sulfonated polyaromatic dye Cibacron blue F3GA. The dye does not have any effect on the estradiol binding site. Additon of the dye to preformed estradiol--receptor--oligo(dT)-cellulose complex results in the release of estradiol--receptor. The inhibition of binding is competitive with respect to oligo(dT)- or oligo(dA)-Celluloses, suggesting that the effect of the dye is directly on the polynucleotide binding site of the receptor. The observed inhibitory effect of Cibacron blue is not a simple electrostatic effect of polyanions because heparin and polyglutamic acid are much less effective. The selective inhibition by Cibacron blue suggests that the polynucleotide binding domain of estradiol--receptor possesses a special "supersecondary" structure [Stellwagen, E. (1977) Acc. Chem. Res. 10, 92--98].